Preservation of Historical Information through Library Services (Case Study of the Library of the Bachelorwiyata Tamansiswa University) - Rosiana Nurwa Indah (Jurnal Mantik, 2022)
This research is entitled "Preservation of Historical Information Through Library Services: A Case Study of the Library of the University of Sarjanawiyata Tamansiswa". The purpose of this research is to find out how the efforts of the Bachelorwiyata Tamansiswa University Library in preserving historical information in the form of Ki Hajar Dewantara's teachings in the current era through various service breakthroughs that it creates. The method used in this research is qualitative method. The method approach used is a case study. Data collection techniques used are through observation, interviews, and document review. The informants in this study amounted to four people, namely the Head of the Library of Sarjanawiyata Tamansiswa University, and library users. The results obtained in this study are the library has been able to seek and realize its role in preserving the historical information of Ki Hajar Dewantara's teachings. The library's efforts are to package the historical information through Student Affairs and Ki Hajar Dewantara Corner services which are supported by multimedia devices; room for discussion and/or learning activities; converting collections in digital form; reprint collections that are no longer published; cooperate with the Taman Siswa museum; and provide resource persons for discussion for researchers.